High Security Differential Chaos-Based Modulation With Channel Scrambling for WDM-Aided VLC System - Bingjun Chen; Lin Zhang; Huaiyin Lu (IEEE Photonics Journal, 2016)
Visible light communication (VLC) systems have relatively higher security compared with traditional radio-frequency (RF) channel thanks to line-of-sight (LOS) propagation. However, due to the broadcasting property of optical channels, VLC systems may also suffer from malicious attacks or eavesdropping. In this paper, we present a differential chaos-based modulation with channel scrambling (DCM-CS) for wavelength-division multiplexing (WDM) aided VLC system to enhance the transmission security over red, green, and blue (RGB) channels. The proposed scheme exploits the diversity property of light emitting diodes (LED) and the natural high-security property of chaotic sequences being sensitive to the initial value and nonperiodic. At the transmitter, the binary phase shift keying (BPSK) symbols are modulated by the chaotic sequences differentially, then the modulated information-bearing chaotic signals and the corresponding reference chaotic sequences are converted to nonnegative signals and transmitted over RGB channels. It is noticeable that the RGB channels change dynamically and are equivalently scrambled, where the secrecy information is shared in an uncoordinate way between the transmitters and legitimate receivers; hence, the security is further enhanced. Theoretical bit error rate (BER) and secrecy capacity expressions are derived, and simulation results are provided and compared to prove the benefits achieved by the proposed scheme.